An initial grammar of a Kedah three year old child's speech - Kimball, Linda Amy (Universiti Kebangsaan Malaysia, 1973)
Spoken language is a unique cultural universal of mankind. Once a child starts to speak two word utterances he begins to apply some type of ordering to hierarchy which controls and limits the sequence in which words are spoken. That is, he utilizes a grammar. Most studies of child language concern Indo-European languages. The present investigation concerns a three years and four months old Kedah male child who is learning to speak Malay, a Malayo-Polynesian language. The data analyzed were recorded during a one week visit in the child's home. The data are strictly those of the child's performance since no attempts of his linguistic skill. This paper presents a Chomskyian-type generative (but not transformational) grammar of the child's utterances. The grammar has limited scope and is but an initial step in the study of language acquisition by Kedah Malay children. Fuller grammatical analyses, semantic analyses, and elicitory tests of linguistic competence remain to be done. However, the usual shyness of young Kedah children makes research by an outsider difficult if not impossible. A method of overcoming this problem might be to train members of the child's family, such as school leavers, to gather data. The study of non-Indo-European child language is important for the formulation of a general theory of child language acquisition. Such a general theory can have important practical application to the teaching of foreign language.